Maternity references on the maternal mortality: decision-making pattern perpective - Nilakesuma, Nur Fadjri; Machmud, Rizanda (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: The Research is motivated by the high rate of maternal mortality in the city of Padang. One reason is the delay in the decision making of referral. The pattern of referrral by a midwife decision making is a complicated process that starts with the process of problem identification, problem-solving alternative search, and evaluation of these alternatives. Objective: The purpose of this study is to identify background reference maternity in cases of maternal mortality regarding decision making patterns of midwives in the city of Padang. Methods: This study was a qualitative study using phenomenology. Data collection was done in the work area of Andalas, Kuranji, Pauh, and Nanggalo from May-August 2016. The selection of informants used snowball sampling technique. Qualitative data were collected through in – depth interviews, and secondary data were collected through document review. Analyzed using a fixed comparison method according to Glaser and Strauss. Results: The result of the study shows that the identification of risk factors performed during antenatal care makes midwives decide to refer to hospitals. However, the referral was rejected by the hospital because there was no emergency alert to the mother. When an emergency occurs during labor, the midwife immediately refers to the patient but tends to be in an unstable patient state. Sothe midwife is blamed for not indicating on time. The decision patterns of midwives in referring maternal mothers to maternal mortality cases are influenced by screening of emergency risk factors, the principle of referral and post-referral impacts. Conclusion: Limitations of authority, identification of risk factors, and post-referral impacts make the midwife utterly wrong in making a referral decision.